Au-delà des savoirs - Claire Lapique (Recherches Sociologiques et Anthropologiques)
Since 2020, the Autonomous Communal University of Oaxaca (UACO) has been operating in the state of Oaxaca through sixteen Communal University Centres (CUCs), gathered to defend their way of life and way of thinking, known as comunalidad. The communal university, as a space of contradiction where different logics – communal and imposed – intersect, projects a resistance that goes beyond knowledge to address “civilisational” issues (Martinez Luna, 2013, 2015). It is thus at the heart of political issues. In fact, while community knowledge is sometimes decontextualised and integrated into state or liberal structures, the ways of life that surround it remain marginalised and even threatened. In addition to a sociology of the circulation of knowledge, a sociology of “communication breakdowns” between different regimes of knowledge (Boumediene, 2019) allows us to situate the university as one of the manifestations of community resistance to the mechanisms of capitalist and colonial domination (Merchant, 1980; Federici, 2020).